Methanol Aromatization over Zn and Ce Modified Hierarchical ZSM-5 Catalysts: Effect of Ce as a Promoter. (24th May 2022) - Wei, Zhenhao; Ji, Yufan; Huang, Yiping; Huang, Jingjing; Huang, Yunguo; Yue, Changhai; Li, Junzhou; Tang, Mingwei; Liu, Yunfang; Liu, Hanfei; Zhu, Hao; Zhu, Kai; et al.
Abstract : Zinc (Zn) and cerium (Ce) modified hierarchical ZSM-5 (HZ) catalysts were prepared by incipient wetness impregnation, and their catalytic performances in methanol to aromatics reaction were evaluated in a fixed-bed reactor operating at 400°C under 0.1 MPa and WHSV of 1.0 h −1 . The structure, acidity, and state of Zn species of the Zn/Ce modified HZ catalysts were investigated via several characterization techniques, including XRD, NH3 -TPD, H2 -TPR, nitrogen adsorption, and XPS. The results showed that the aromatization activity of 2 wt% Zn-modified HZ (2% Zn/HZ) could be significantly enhanced by loading 0.6 wt% Ce, which was mainly attributed to the increase in surface ZnOH + species. Moreover, it was found that Ce inhibited pore blockage caused by Zn. Consequently, compared to 2% Zn/HZ, 2% Zn-0.6% Ce/HZ exhibited higher aromatic selectivity and longer catalyst lifetime.